Light adaptation and the evolution of vertebrate photoreceptors - Morshedian, Ala (J Physiol, 2017)
KEY POINTS: Lamprey are cyclostomes, a group of vertebrates that diverged from lines leading to jawed vertebrates (including mammals) in the late Cambrian, 500 million years ago. It may therefore be possible to infer properties of photoreceptors in early vertebrate progenitors by comparing lamprey to other vertebrates. We show that lamprey rods and cones respond to light much like rods and cones in amphibians and mammals. They operate over a similar range of light intensities and adapt to backgrounds and bleaches nearly identically. These correspondences are pervasive and detailed; they argue for the presence of rods and cones very early in the evolution of vertebrates with properties much like those of rods and cones in existing vertebrate species. ABSTRACT: The earliest vertebrates were agnathans – fish‐like organisms without jaws, which first appeared near the end of the Cambrian radiation. One group of agnathans became cyclostomes, which include lamprey and hagfish. Other agnathans gave rise to jawed vertebrates or gnathostomes, the group including all other existing vertebrate species. Because cyclostomes diverged from other vertebrates 500 million years ago, it may be possible to infer some of the properties of the retina of early vertebrate progenitors by comparing lamprey to other vertebrates. We have previously shown that rods and cones in lamprey respond to light much like photoreceptors in other vertebrates and have a similar sensitivity. We now show that these affinities are even closer. Both rods and cones adapt to background light and to bleaches in a manner almost identical to other vertebrate photoreceptors. The operating range in darkness is nearly the same in lamprey and in amphibian or mammalian rods and cones; moreover background light shifts response–intensity curves downward and to the right over a similar range of ambient intensities. Rods show increment saturation at about the same intensity as mammalian rods, and cones never saturate. Bleaches decrease sensitivity in part by loss of quantum catch and in part by opsin activation of transduction. These correspondences are so numerous and pervasive that they are unlikely to result from convergent evolution but argue instead that early vertebrate progenitors of both cyclostomes and mammals had photoreceptors much like our own.